(3GdEbJUGO GdSjGSj (B/s - (3SdWGf, GSeGYjd eMeOs ((3YeGf(B: s (3OGQ GdQGjI ddfTQ hGdJhRjY(B, s, 2013)
(3eaGgje EbJUGOjI(B- (3YdGbI GdEbJUGO GdSjGSj HGdJfejI GdSjGSjI hGdEbJUGOjI(B- (3GdJfejI GdEbJUGOjI hGdJNWjW GdEbJUGOj(B- (3JLGQH aj Mbd GdJNWjW hGdJfejI GdEbJUGOjI hHfGA GdEbJUGO GdSjGSj(B- (3cjajI HfGA hJMbjb GdEbJUGO GdSjGSj hGdYhGFb hGdeTcdGJ(B- (3JSjS GdEbJUGO GdNGQLj hGdgjefI hGdJHYjI(B- (3GdEbJUGO GdSjGSj aj GdfXGe GdESdGej(B- (3GdYhdeI GdEbJUGOjI hBKGQgG Ydi GdEbJUGO GdSjGSj(B- (3efXeI GdJLGQI GdYGdejI(B- (3GdEbJUGO GdSjGSj hGdYdGbGJ GdOhdjI GdSjGSjI(B- (3GdEbJUGO GdSjGSj aj GdYdGbGJ GdOhdjI GdYGeI GdNGQLjI(B- (3GdEbJUGO GdSjGSj aj GdYGde GdYQHj(B- (3OhQ GdEYdGe aj GdEbJUGO GdSjGSjs
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdSjGSjs; (3GdSjGSIs